Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper analyzes the effect of aging on pension expenditure in Luxembourg. The paper highlights that Luxembourg is in a relatively favorable position because its GDP growth has been well above the average for industrialized countries in the post-war period. Moreover, growth has been unconstrained in that much of it has been based on the influx of foreign capital and labor. The paper provides some illustrative simulations of pension expenditure in Luxembourg, and describes the demographic developments. After reviewing methodological issues, simulations of pension expenditure until 2050 are also presented.